2005
DOI: 10.1007/bf02859264
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety evaluation of cefaclor VS amoxycillin + calvulanate in children with Acute Otitis Media (AOM)

Abstract: Acute Otitis Media (AOM) is the most frequent respiratory tract infection of infancy and childhood that is treated with antimicrobial agents. The most common causative pathogens include Streptococcus pneumoniae, Hemophilus influenzae and Moxarella catarrhalis, and therefore antibacterial management should target against these isolates. Cefaclor, a congener of cephalexin monohydrate, is a semisynthetic cephalosporin antibiotic. It is an orally active cephalosporin which has demonstrated activity against a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Part of this uncritical acceptance is the belief that they, slum residents, after all, are better off than rural residents. Besides, it is also acknowledged that all slums are not equal and variations in health status among slum population groups are as evident as variations across rural communities (8). …”
Section: Introductionmentioning
confidence: 99%
“…Part of this uncritical acceptance is the belief that they, slum residents, after all, are better off than rural residents. Besides, it is also acknowledged that all slums are not equal and variations in health status among slum population groups are as evident as variations across rural communities (8). …”
Section: Introductionmentioning
confidence: 99%
“…Recent research has also indicated that slums may be more heterogeneous than is often assumed (Goli et al, 2011, Chandrasekhar and Montgomery, 2009, Agarwal and Taneja, 2005); many poor people like pavement dwellers do not live in slums and are therefore not “counted” by the standard definitions (Agarwal, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Heikkinen et al found that Streptococcus pneumonia, Hemophilus influenza and Moraxella catarrhalis were the most common bacterial pathogens that cause AOM 25%, 23% and 15% respectively [1]. Acute otitis media is one of the most common diseases to be treated with antimicrobial drugs in pediatric population, accounting for 25-50% of the oral antibiotics prescribed annually [19]. The use of antibiotics in the treatment of acute otitis media remains a controversial area in medical practice.…”
Section: Discussionmentioning
confidence: 99%